Determinasi Pendapatan, Ability to Pay, dan Jumlah Tanggungan terhadap Beban Biaya Kesehatan Peserta BPJS Mandiri: Studi pada Pedagang Pasar Passo - Mersy Delty Kainama; Pollan Versilia Wuritimur; Minnalia Soakakone (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The National Health Insurance (JKN) is a program of the Indonesian government that, in principle, aims to provide health insurance for the Indonesian people. In Indonesia, people are at risk of catastrophic health payments, namely if health payments exceed 10% of household income. From a government perspective, government spending on health reaches 0.9% of GDP in Indonesia, much lower than Thailand (2.9%), China (2.7%), and Vietnam (2.6%). The purpose of this study was to determine the factors associated with the burden of health costs for families of BPJS Kesehatan Mandiri participants among traders in Passo Market. The research method in this study was quantitative with a cross-sectional approach. The results of the study indicate a relationship between income and the burden of health costs for independent BPJS participants with a P value of 0.044, with the average feeling of having a high cost burden being those with incomes <UMR. This study also shows a relationship between Ability to Pay (ATP) and the burden of health costs for independent BPJS participants with a P value of 0.047, with the average being unable to pay and feeling they have a high burden. This study also shows a relationship between the number of family members and the burden of health costs for independent BPJS participants, with the average number of family members being >5. Thus, Passo market traders, most of whom are independent BPJS participants, feel that they have a greater burden in financing their health.